-18-6x=(1-+3x)

Simple and best practice solution for -18-6x=(1-+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18-6x=(1-+3x) equation:



-18-6x=(1-+3x)
We move all terms to the left:
-18-6x-((1-+3x))=0
We add all the numbers together, and all the variables
-6x-((+3x))-18=0
We calculate terms in parentheses: -((+3x)), so:
(+3x)
We get rid of parentheses
3x
Back to the equation:
-(3x)
We add all the numbers together, and all the variables
-9x-18=0
We move all terms containing x to the left, all other terms to the right
-9x=18
x=18/-9
x=-2

See similar equations:

| 13/9=13/x+3 | | 2(5n+3)=46-14n | | f(10)=-2+13 | | 15x=17+6x | | 7p^2+17p=-6 | | k/5+9=6 | | 12=8−–r | | 3/5(x-6)=15 | | -6/r+7/r-2=5 | | 14-8x=-(-8+3x)+1 | | -⅔(6x+9)=-7x+3x | | g-82/6=2 | | 12n-6=12n+6 | | 8y-4y-5=37.88 | | -5+p/2=-2 | | 24y+36=24y | | 14x+6=-2 | | 8y-4y-5=37.88. | | 5s-(-21)=51 | | 3x-6=4+2x | | 4y/9=-20 | | 4(2k-2)=3k-13 | | -y=35-85 | | 10=n2+ 7 | | 3x-7=3(x-4)+1 | | 20-6w-3w=4(15-w) | | {−1.5m=−2.55} | | 11-x=167 | | a-26-9=7 | | 53=4-(-7)s | | 6-5p=6-4p-10p | | -12=3-7x+2x |

Equations solver categories